The Causal Factors and Problem Solving of Biology Lab Work Obstacles at Senior High Schools - Nur Rahmah; Iswadi Iswadi; Asiah Asiah; Hasanuddin Hasanuddin; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
ABSTRACT          This study aims to determine the causal factors of obstacles lab work, and to find alternative solutions. This research was done on march until july 2020. The method in this study was carried out by means of a questionaire and literature review. Sample in this study were 11 SMA in Banda Aceh, with respondents 11 biology teachers teaching class XI and 99 students of class XI IPA. The data was analyzed using a percentage formula. The results of this research showed that the constraints for practical implementation included inadequate supporting facilities, lack of completeness of practicum materials, insufficient time allocation for practicum, lack of readiness of laboratory assistants in prepared practicum tools and materials, absence of laboratory assistants in several sample schools, and some biology teachers or laboratory assistants in sample schools have never attended training on practicum or the use of laboratory equipment. Solutions that can be given in overcoming the constraints of practicum implementation are applying for laboratory development funding assistance to related parties, planning time allocation properly, finding laboratory assistants by the school and holding training for teachers and laboratory assistants regarding laboratory techniques and laboratory management.Keywords: obtacles, lab practice, biologyABSTRAK          Penelitian yang dilakukan di SMA Kota Banda Aceh bertujuan untuk mengetahui faktor penyebab kendala praktikum dan mencari solusi alternatif penyelesaiannya. Penelitian dilakukan pada bulan Maret-Juli tahun 2020. Metode penelitian ini dilakukan dengan cara angket dan kajian literatur. Sampel dalam penelitian ini adalah 11 SMA di Kota Banda Aceh, dengan responden 11 guru biologi yang mengajar kelas XI dan 99 peserta didik kelas XI IPA. Analisis data menggunakan rumus persentase. Hasil dari penelitian diketahui faktor kendala pelaksanaan praktikum diantaranya, fasilitas pendukung yang tidak memadai, minimnya kelengkapan bahan praktikum, alokasi waktu praktikum tidak mencukupi, kurangnya kesiapan laboran dalam mempersiapkan kebutuhan praktikum, tidak adanya laboran di beberapa sekolah sampel, dan sebagian guru biologi/laboran di sekolah sampel belum pernah mengikuti pelatihan mengenai praktikum atau penggunaan alat laboratorium. Solusi yang dapat diberikan dalam mengatasi kendala pelaksanaan praktikum adalah dengan merencanakan alokasi waktu dengan baik, mencari tenaga laboran oleh pihak sekolah serta mengadakan pelatihan kepada guru dan laboran mengenai teknik laboratorium dan pengelolaan laboratorium.Kata Kunci: kendala, praktikum, biologi